Design and implementation of a dc-dc converter based on variable structure control of switched systems - Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C.M. [UNESP]; Assunção, Edvaldo [UNESP]; Covacic, Márcio R.; De Seixas, Falcondes J.M. [UNESP]; Faria, Flávio A. [UNESP]; Mainardi Jr., Edson I. [UNESP] (Elsevier, 2011)
This paper presents a control method for a class of continuous-time switched systems, using state feedback variable structure controllers. The method is applied to the control of a non-trivial dc-dc power converter and a simple and inexpensive control circuit design, that was simulated using the software PSpice, is proposed. The design is based on Lyapunov-Metzler-SPR systems and the performance of the resulting control system is superior to that afforded by a recently proposed alternative sliding-mode control technique. © 2011 IFAC.
Keywords: DC-DC converters; LMIs; Lyapunov-Metzler inequalities; Strictly positive real systems; Switched systems; Variable structure control; Continuous time; Control circuits; Control methods; DC-DC power converter; Non-trivial; Strictly positive real; Switched system; Variable structure controller; SPICE; State feedback; Switching systems